Nilai Moral Tanggung Jawab Dalam Buku Legenda Putri Cermin Cina Karya Ilsa Dewita Putri Soraya - Khotimah, Nurul; Wilyanti, Liza Septa; Adiyadmo, Dimas Anugrah (Universitas Batanghari Jambi, 2025)
This study aims to examine the moral value of responsibility in the legend Putri Cermin Cina by Ilsa Dewita Putri Soraya using a descriptive qualitative approach and structural analysis. As a form of traditional literature, legends not only convey historical and mythological stories but also contain moral messages that serve as life guidance. The main focus of this research is how the value of responsibility is portrayed through the main character. The results show that the protagonist demonstrates a strong sense of responsibility toward family, society, and moral principles, reflected in courageous, honest, and self-sacrificing actions. These actions illustrate a moral awareness that develops from mere compliance with externalrulestoresponsibilitydrivenbyconscience.Suchvaluesarehighlyrelevant in the context of character education, particularly in shaping students with integrity and ethical awareness. Therefore, the legend Putri Cermin Cina holds significant potentialasamediumformorallearninginbothformalandnon-formaleducational.